Types of Lexical Cohesion and Grammatical Cohesion in Thesis Abstracts - Rena Puspa Kirana; Mukhrizal Mukhrizal; Fernandita Gusweni Jayanti (Yayasan Karinosseff Muda Indonesia, 2020)
This research attempted at investigating the types of lexical cohesion and grammatical cohesion used in thesis abstracts composed by undergraduate English department students of Universitas Bengkulu and also the errors of using cohesion. The research was designed as a descriptive quantitative method. The corpus of this study was 30 thesis abstracts composed by undergraduate English department students of Universitas Bengkulu. The instrument of this research was self-developed checklist. In analyzing data, the researchers were using formula by Sugiono. The results of this research showed that : 1.) There were 458 as the total number of six lexical cohesion types found in 30 thesis abstracts and the most dominant type is Repetition (58.7%). 2.) There were 783 as the total number of four grammatical cohesion types found in 30 thesis abstracts and the most dominant type is Reference (70.2%). 3.) There werere three errors of using cohesion namely omission of conjunction and selection of conjunction. Therefore, it was concluded that the thesis abstracts composed by undergraduate English department students of Universitas Bengkulu were in the percentage of 99.76% good.